Monetary Indexation and Revenues from Money Creation : The Case of Iceland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper discusses the effects of monetary indexation on the revenues from monetization in Iceland. The paper starts by showing that monetization revenues fell sharply after indexation was introduced in 1979 and evaluates the different and partly ambiguous factors behind this development. The fiscal consequences are then examined in light of the fact that revenues from monetization have traditionally made up a substantial part of Government revenues in Iceland. Different policy options are simulated using the framework of the public finance approach to inflation. The simulations focus on the relation of fiscal deficits to inflation, output growth, and internal and external debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet